2018
DOI: 10.1016/j.cortex.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The cerebellar topography of attention sub-components in spinocerebellar ataxia type 2

Abstract: Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant neurodegenerative disease characterized by a progressive cerebellar syndrome and multiple-domain cognitive impairments. The cerebellum is known to contribute to distinct functional networks related to higher-level functions. The aims of the present study were to investigate the different sub-components of attention and to analyse possible correlations between attention deficits and specific cerebellar regions in SCA2 patients. To this purpose, 11 SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…These previous studies are in line with our results. More generally, brain–behavior relationships between these specific posterior cerebellar regions and cognitive inhibition or executive tasks implying cognitive inhibition have also been reported: Stroop test and GM volume in the vermis crus II,43 go/no-go task and GM volume in the vermis lobule VI44 and finally, Wisconsin Card Sorting task and GM volume in the vermis VIIb 43. Finally, a recent study has also shown that transcranial direct current stimulation over the medial cerebellum reduced the percentage of errors during a go/no-go task 45…”
Section: Discussionmentioning
confidence: 88%
“…These previous studies are in line with our results. More generally, brain–behavior relationships between these specific posterior cerebellar regions and cognitive inhibition or executive tasks implying cognitive inhibition have also been reported: Stroop test and GM volume in the vermis crus II,43 go/no-go task and GM volume in the vermis lobule VI44 and finally, Wisconsin Card Sorting task and GM volume in the vermis VIIb 43. Finally, a recent study has also shown that transcranial direct current stimulation over the medial cerebellum reduced the percentage of errors during a go/no-go task 45…”
Section: Discussionmentioning
confidence: 88%
“…In recent years, an increasing body of studies focused on the cerebellar role in cognitive functions and emotional regulation also including social cognition abilities [1][2][3][4][5][6][7][8][9][10]. From an anatomical point of view, research documented the existence of reciprocal connections between specific cerebellar regions and associative and paralimbic cerebral structures related to emotional and social processing such as the temporo-parietal junction (TPJ), the lateral temporal cortex, the posterior cingulate cortex, the inferior frontal gyrus [11], the amygdala [12] and the insula [13].…”
Section: Introductionmentioning
confidence: 99%
“…Upon her re-admission 1 month later, the patient's major complaint was worsening of the ataxia and an increased cognitive-emotional deficit. In recent years, increasing evidence for a role for the cerebellum in emotion and cognition has emerged [8][9][10][11][12] and the patient was identified as having cerebellar cognitive affective syndrome [13]. The default mode network (DMN) has become the primary and most popular target of resting state networks and is thought to be involved in advanced cognitive functions and emotion [14][15][16].…”
Section: Case Presentationmentioning
confidence: 99%